Trends in the discipline of Information Visualization - Pérez-Montoro, Mario (Anuario ThinkEPI, 2022)
Evolution overview of the discipline of information visualization during 2021. We select, on the one hand, various proposals that incorporate innovations regarding visual concepts and resources, and on the other, some examples of visualizations that have attracted attention, not so much for their visual contributions but for the set of data and content they have represented. Finally, to complete this vision of the evolution of this discipline over one year, we address some advances related to the technological development in the field of information visualization.